GENETIC ENGINEERING AND ITS IMPORTANCE IN BIOTECHNOLOGY - Umida Otabekovna Makhamatjonova (Bright Mind Publishing, 2026)
This article examines genetic engineering and its importance in biotechnology. Specifically, it covers the concept, history, and main methods of genetic engineering. The application, advantages, and potential challenges of genetic engineering in medicine, agriculture, industry, and ecology are discussed. Information on the capabilities and prospects of modern gene editing technologies is also provided.
Keywords: Biotechnology, genetic engineering, recombinant DNA, gene editing, genetically modified organisms, biological products, biotechnology in medicine, biotechnology in agriculture.